Crustal Structure and Tectonic Origin of Late Cretaceous Oceanic Crust and Adjacent Caribbean Large Igneous Province in the Colombian Basin - Juan Pablo Ramos; Paul Mann; Luis Carlos Carvajal‐Arenas (Geochemistry, Geophysics, Geosystems)
Abstract The tectonic origin of the Caribbean Large Igneous Province (CLIP) and its adjacent oceanic crust in the Colombian Basin are examined using 3D seismic reflection mapping, regional gravity and magnetic data mapping, and a compilation of CLIP radiometric ages. Using these data, we show how the CLIP and its adjacent oceanic crust formed by extensive and prolonged volcanism linked to a regional, east‐west trending, extinct spreading ridge. Our 3D seismic mapping of the crustal structure in the Colombian Basin shows a northeast‐striking transform fault separating two extinct ridge segments based on the abrupt shallowing (>10 km) of the Moho, and the changes in crustal thickness from 16 km to <4 km. Additional 3D mapping combined with mapping of regional gravity anomalies reveals other northeast‐trending transform faults that offset the east‐west‐trending spreading ridge system. Integration of previously studied magnetic anomalies suggests that seafloor spreading in the Colombian and Venezuelan basins occurred during the primary period of CLIP formation from the Albian to Campanian (108–73 Ma). The presence of seaward dipping reflectors mapped using the 3D seismic reflection data further supports our hypothesis that the thickened crust of the CLIP accompanied seafloor spreading along the newly identified spreading ridge. The ages of CLIP basalts recovered from outcrops and offshore samples support our conclusions that the CLIP is largely the product of volcanic eruptions along a spreading ridge system over a period of 30 My and that the areas of normal oceanic crust adjacent to the spreading ridge records a gradual reduction in the magma supply to the spreading ridge.